The Protection of Geographical Indications: Law and Practice by Michael Blakeney - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2015)
Since the adoption of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) in 1994, the topic of geographical indications of origin (GIs) has divided members of the international community. Twenty years on, controversy remains strong and hopes to reach an international consensus are small. Paradoxically, introducing GI protection as an action item in the Doha Development round of the World Trade Organization (WTO) in 2001—in order to advance the negotiations on GIs pursuant to TRIPS’s built-in agenda—contributed to gridlock the debate within the WTO. Yet, 2015 is likely to become a turning point in the international GI debate. Notably, attention to GIs has been growing in many fora during the recent months. In particular, GIs have become an item of note within several bilateral and plurilateral international free trade agreements (FTAs). Moreover, a growing number of countries are increasingly interested in GIs as suitable mechanism to protect and promote products from their regions. A renewed "GI buzz" has also reached the World Intellectual Property Organization (WIPO), with intense discussions over a revival of the 1958 Lisbon Agreement for the Protection of Appellations of Origin (Lisbon Agreement) as a possible way to resolve the international impasse on the regulation of GIs. A Diplomatic Conference for the Adoption of a New Act of the Lisbon Agreement will take place in Geneva in May 2015. Despite this renewed attention to GIs, however, the legal literature on GIs is still scarce, at least from a practitioners’ perspective. In particular, existing publications tend to focus on the academic discussion over GIs, especially on the controversy surrounding the scope, the means, and even the definition of GIs. Economists and sociologists have also analysed GIs, but primarily as tools for economic and social development from a public policy perspective. For these reasons, the book The Protection of Geographical Indications: Law and Practice by Professor Michael Blakeney is an important contribution to the existing literature, especially for attorneys who represent clients involved in GI-related disputes. This book adds a much-needed practical *334 perspective to the law of GIs, including with respect to the provisions on the enforcement of GI protection and the law of passing off as it applies to geographical names in the UK and other common law countries. Focusing primarily on the law on GIs in the EU, the book guides readers through the histories, legal developments, and the updated version of the European Regulation on GIs. In this context, the book meticulously recounts the leading cases by the Court of Justice of the EU (CJEU). The book is divided into seven chapters. Chapter 1 is an Introduction, which summarises the history, economics and the definitions of GIs. Chapter 2 describes the international framework of GI protection. Chapters 3 to 5 explore the substantive analysis of the law of GIs in the EU. The two remaining chapters focus on the co-existence (and conflict) between GIs and trade marks, and on the enforcement provisions applicable to GIs. In this review, I offer some observation on the content of Chs 2–7.